2016
DOI: 10.2967/jnumed.115.169888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radioiodine Treatment on Salivary Gland Function in Patients with Differentiated Thyroid Carcinoma: A Prospective Study

Abstract: Complaints of a dry mouth (xerostomia) and sialoadenitis are frequent side effects of radioiodine treatment in differentiated thyroid cancer (DTC) patients. However, detailed prospective data on alterations in salivary gland functioning after radioiodine treatment ( 131 I) are scarce. Therefore, the primary aim of this study was to prospectively assess the effect of high-activity radioiodine treatment on stimulated whole saliva flow rate. Secondary aims were to study unstimulated whole and stimulated glandular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 21 publications
1
51
0
Order By: Relevance
“…3 Dry mouth (xerostomia) and sialoadenitis remain frequent side effects of radioiodine treatment, especially in patients treated with high acitivities. 50 In our study, the number of treatments and the cumulative dose of radioiodine administered are high; this can be explained by the very long period of recruitment (about 35 years), including years when few therapeutic alternatives were available and different guidelines were adopted (e.g., no conservative approach for early stage disease or the absence of some radioiodine alternative options like tyrosine-kinase inhibitors).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…3 Dry mouth (xerostomia) and sialoadenitis remain frequent side effects of radioiodine treatment, especially in patients treated with high acitivities. 50 In our study, the number of treatments and the cumulative dose of radioiodine administered are high; this can be explained by the very long period of recruitment (about 35 years), including years when few therapeutic alternatives were available and different guidelines were adopted (e.g., no conservative approach for early stage disease or the absence of some radioiodine alternative options like tyrosine-kinase inhibitors).…”
Section: Discussionmentioning
confidence: 86%
“…None of these prophylactic measures have yet been formally studied in the pediatric population . Dry mouth (xerostomia) and sialoadenitis remain frequent side effects of radioiodine treatment, especially in patients treated with high acitivities …”
Section: Discussionmentioning
confidence: 99%
“…[31] Furthermore, salivary gland stem cells, which have been proposed to mainly reside in the excretory ducts, [32] may also be affected because of the exposure to β radiation resulting in a reduced regenerative potential. [33] …”
Section: Discussionmentioning
confidence: 99%
“…For instance, Klein Hesselink et al [8] showed the salivary gland damage varied with the sensitivity of the patients to the radiation and the cumulative dose of 131 I. Some reports demonstrated that acute sialadenitis could happen in as many as 15% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…All 18 patients suffered from radiation‐induced xerostomia: seven male patients after radioligand therapy of metastasized prostate cancer (tumor‐specific radioligand therapy that binds to prostate‐specific membrane antigen [PSMA], lutetium‐177 PSMA‐617 ‐[LuPSMA]) and 11 (two males and nine females) after radioiodine therapy due to thyroid cancer. Xerostomia is a common side effect of both therapies (Heck et al, ; Klein Hesselink et al, ). Twenty‐one patients with impaired hearing formed the “non‐xerostomia group.” Excluded were patients aged <18 years and those not being fluent in German language.…”
Section: Methodsmentioning
confidence: 99%